Syntactic analysis of scenic spaces: the case of Praça do Comércio in Lisbon - Fernandes, Pedro Afonso (2022)
Space syntax is a set of theories and techniques for analysing urban settlements and buildings. Focused on the study of the configuration of convex spaces, spatial syntax may have some difficulty in incorporating qualitative or sensory aspects of urban space. In particular, the scenic dimension associated with certain urban morphologies, such as squares or plazas, may coexist in less integrated spaces, though some association with high visibility areas is foreseeable. In this article, a two-step strategy was adopted in order to identify the typical syntactic characteristics of scenic spaces supported by the case study of Praça do Comércio, located in Lisbon’s historic centre, Portugal. Starting from the premise that scenic spaces are usually gifted with landmarks or edges, as defined by Lynch, we begin by recalling the relationship between syntactic elements and legible elements, following the seminal work of Dalton and Bafna. Then, an assessment of the scenic features of the legible elements of Praça do Comércio is carried out, suggesting some association between scenic spaces, visual connectivity and axial integration. The validity of control’s reciprocal as a possible syntactic measure of the scenic features of space is also tested, noting that the relationship between stage and audience is inverse to that established between the guard and prisoners in the Panopticon, a type of building where control is maximized.